Kinerja Teknologi Budidaya Jagung Hibrida di Indonesia - TRI HASTINI; IRMA NOVIANA (Agrotrop : Journal on Agriculture Science, 2020)
The performance of hybrid maize cultivation technology in Indonesia. Maize is the most important crop after rice. Beside as a food, maize has other functions as forage and raw material of bioethanol. In Indonesia, the need of maize increases every year. To fulfil the need, an appropriate breakthrough that can increase maize production significantly, is required. The most popular breakthrough is the use of hybrid variety, that is the first generation derived from two or more pure lines crossing. This review discusses the results of hybrid maize researchs and assessments at various types of agroecosystem. Maize hybrid variety planting accompanied by the appropriate location specific technologies could increase maize productivity significantly.